2018
DOI: 10.1111/and.13141
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of heavy metal effects on sperm function using computer-aided sperm analysis and cytotoxicity assays

Abstract: One known environmental risk factor impacting on human reproduction is heavy metal pollution. Although some metals (e.g., Cu, Se and Zn) have protective effects on the male reproductive system in low doses, heavy metals can accumulate to toxic levels and result in poor semen quality and decreased sperm function. We investigated the effect of CuSO and CdCl (10, 50, 100 and 250 µg/ml or 500 µg/ml) on human sperm motility and vitality by using computer-aided sperm analysis (CASA) and two cytotoxicity assays (WST-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…In vitro Cd-exposed murine spermatozoa exhibit an altered sperm fertilization potential, producing a lower number of pronuclei than controls during in vitro fertilization [ 37 ]. A severe reduction of sperm motility and kinematic parameters was also shown in a rat model exposed to Cd in vivo [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro Cd-exposed murine spermatozoa exhibit an altered sperm fertilization potential, producing a lower number of pronuclei than controls during in vitro fertilization [ 37 ]. A severe reduction of sperm motility and kinematic parameters was also shown in a rat model exposed to Cd in vivo [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Cd concentration in the human seminal plasma is closely related to working conditions, food and cigarette smoke, with a reduced fertility being observed in highly exposed patients [ 34 ]. In vitro studies have shown that Cd affects sperm motility and the sperm’s ability to reach and penetrate into the oocyte [ 35 , 36 , 37 , 38 ]. Furthermore, rats exposed to Cd showed a reduced testicular volume sperm concentration and testosterone concentration in the Leydig cells, as well as an increased follicle-stimulating hormone (FSH) concentration in the serum [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metals such as Hg, Pb, tin (Sn), silver (Ag), bismuth (Bi) and indium (In), showed an inhibition of sperm creatine kinase, probably causing male infertility [ 74 ]. Some motility parameters were significantly lowered after the exposure to high concentrations of copper sulfate (CuSO 4 ) and cadmium chloride (CdCl 2 ) [ 75 ]. In addition, lead was found to inhibit human sperm functions by diminishing the levels of the sperm intracellular cyclic adenosine monophosphate (cAMP), calcium and protein tyrosine phosphorylation [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lots of men diagnosed with infertility are experiencing different semen abnormalities such as low sperm count, low sperm motility, and impaired sperm function that resulting in incapability to fertilize an oocyte in the absence of explicit etiologic factors [2]. For decades, human semen quality has been degraded due to potential factors including air pollutants or toxicants, obesity, smoking, drinking, electromagnetic waves from cell phones, and dietary factors [3][4][5][6][7][8][9]. Studies regarding male infertility covered a wide range and aimed to explore the mechanism of the disease at molecular and biochemical levels [10].…”
Section: Introductionmentioning
confidence: 99%